Computer-aided generation of fixture configuration design using polychromatic sets. (17th July 2007) - Ji, P.; Lau, Francis K.H.; Jiang, Lili; Li, Min; Li, Zhongbin
This paper presents a new approach to the generation of fixture configuration design in manufacturing. First of all, the concept of polychromatic sets is introduced. Then the polychromatic set approach to the generation of fixture configuration design is proposed. This approach first identifies the relationship between fixture elements and then derives a contour matrix and its corresponding Boolean matrix. Furthermore, feasible paths and final alternatives to the fixture configuration design are found using the theory of polychromatic sets. A fixture configuration design example is used to illustrate the approach.